Corporate Social Responsibility Analysis Through Shariah Enterprise Theory Approach in an Effort to Realize Good Corporate Governance - Sulinda Nur R; Novi Puspitasari (Lembaga Intelektual Muda (LIM) Maluku, 2022)
The purpose of this study is to analyze the implementation and disclosure of Corporate Social Responsibility (CSR) at Bank Muamalat Indonesia (BMI) with the concept of Shariah Enterprise Theory in an effort to realize Good Corporate Governance (GCG). This study uses descriptive qualitative research methods with Bank Muamalat Indonesia (BMI) as the object of research. The data collection method used is a document study, while the data source in this study comes from secondary data, obtained through the BMI anual report in 2012, especially the CSR and GCG BMI reports in 2012. The result of this study is that BMI has applied the concept of Shari'ah Enterprise Theory to its social activities with regard to vertical accountability and horizontal accountability (inderect stakeholders and nature) on its social responsibility report. As for horizontal accountability to derect stakeholders explained in the corporate governance report on human resources, but the application of horizontal accountability to nature is still very little. The application of sharia enterprise theory concept to the implementation and disclosure of BMI CSR has an impact on social activities carried out will be based on the law or Islamic shari'ah to get the pleasure of Allah and to create GCG on BMI. In addition, the concept of Shari'ah Enterprise Theory can also be used to understand GCG in shari'ah banking